Fruits, vegetables and breast cancer risk: a systematic review and meta-analysis of prospective studies - Aune, D.; Chan, D. S. M.; Vieira, A. R.; Rosenblatt, D. A. Navarro; Vieira, R.; Greenwood, D. C.; Norat, T. (Breast cancer research and treatment, 2012)
Evidence for an association between fruit and vegetable intake and breast cancer risk is inconclusive. To clarify the association, we conducted a systematic review and meta-analysis of the evidence from prospective studies. We searched PubMed for prospective studies of fruit and vegetable intake and breast cancer risk until April 30, 2011. We included fifteen prospective studies that reported relative risk estimates and 95 % confidence intervals (CIs) of breast cancer associated with fruit and vegetable intake. Random effects models were used to estimate summary relative risks. The summary relative risk (RR) for the highest versus the lowest intake was 0.89 (95 % CI: 0.80–0.99, I 2 = 0 %) for fruits and vegetables combined, 0.92 (95 % CI: 0.86–0.98, I 2 = 9 %) for fruits, and 0.99 (95 % CI: 0.92–1.06, I 2 = 20 %) for vegetables. In dose–response analyses, the summary RR per 200 g/day was 0.96 (95 % CI: 0.93–1.00, I 2 = 2 %) for fruits and vegetables combined, 0.94 (95 % CI: 0.89–1.00, I 2 = 39 %) for fruits, and 1.00 (95 % CI: 0.95–1.06, I 2 = 17 %) for vegetables. In this meta-analysis of prospective studies, high intake of fruits, and fruits and vegetables combined, but not vegetables, is associated with a weak reduction in risk of breast cancer.